The effect of cortical neural stimulation on elite performers - Carrillo, A. E.; Flouris, A. D. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Previous scientific findings suggest that listening to music and performing spatial tasks co-utilize neural pathways [1]. Specifically, listening to Mozart`s Sonata for Two pianos (K. 448) has shown significant positive effects in spatial-temporal reasoning, known as the "Mozart Effect" [2]. The present study investigated the effects of the specific neural stimulus on precise performance tasks completed by elite athletes. Methods A repeated-measures, randomized block design required 26 elite male soccer players (12-16 yrs.) and 24 elite male cricket players (14-17 yrs.) to execute both spatial-temporal organization speed and skill drills. Speed performance was determined by recording the amount of time required to complete the task whereas the achieved score upon completion of the skill task measured skill. Each drill was executed twice on 2 different days, which also incorporated a 10-minute rest period prior to testing. Mozart`s Sonata was randomly implemented throughout one of the two testing sessions, with no stimulation implemented during the other testing period. Results ANOVA indicated that performance in the skill test was significantly improved in both soccer (p<0.001) (stimuli = 41.76±17.15; non-stimuli = 33.38±15.07) and cricket (p<0.05) (stimuli=10.10±2.54; non-stimuli = 9.07±2.54) following the music stimuli session. However, the stimuli contributed no significant (p>0.05) improvement in speed for either soccer (stimuli=4.90±0.48; non-stimuli=5.01±0.24) or cricket (stimuli = 5.77±0.46; non-stimuli = 6.02±0.58). Discussion/Conclusions The results of the present study suggest that spatial-temporal stimuli can significantly improve skill performance of elite athletes in soccer and cricket. Future research is required to examine whether the "Mozart Effect" can improve performance in competitive sports. Considering the abovementioned results, specific implementation strategies should be designed to further enhance performance. Finally, by varying the listening time and musical compositions, researchers can gain insight on how to optimize the enhancing effect as well as examine the effects of various musical styles.